SILENT CRIES OF INDO-PAKISTANI WOMEN AS PORTRAYED IN NAGA-MANDALA AND KALA MEDA BHES, A COMPARATIVE ANALYSIS OF TWO FEMINIST PLAY - Sarfraz, Danish (ShodhGyan-NU: Journal of Literature and Culture Studies, 2024)
“One is not born a woman, but rather becomes one. Gender is not a stable identity but a performative act constituted by repeated societal norms” (Butler, 1990). The paper under analysis pertains to the two fresh and ground-breaking plays Naga-Mandala and Kala Meda Bhes by Indian and Pakistani playwrights who are quite successful and prolific writers in the arena of South Asian Literature. The aim of this study is to discover the shushed and quietened voices of women in the both plays in one way of the other. The paper is based on a qualitative research with the use of textual method and discourse analysis particularly on both the plays with the help of websites, poems, dictionaries and papers to support this research. The paper will trigger the feminist elements and identity of the Indo-Pakistani women with comparative analysis. Researchers may comprehensively draw two conclusions from this paper i.e. The suppression of the female genders due to male patriarchy in Indo-Pakistani Society and the lack of logical reasoning, supernatural elements and superstitions in both the society as represented in both the plays under-discussion.